A produção teatral escolar como expressão dos valores culturais na adolescência: um estudo de caso - Boone, Sinara Maria (My University, 2014)
The school environment is a place where culture is revealed by the integration of different values. This study aims at analyzing cultural values that are disclosed in adolescents written productions assigned in drama classes. The study analyzed drama scripts presented by students of a private school in Caxias do Sul. The research method was based on content analysis and its corpus is a set of drama scripts produced throughout an 11-year-period, which address to some cultural aspects that are valued among adolescents. From the study it was possible to come up with cultural themes related to family and friends; regional culture; traces of Italian and local (gaucho) cultures; literature; movies and the past; (worries about) the future and the environment; media and technology. The approach of such topics is defined by the aspects expressed in the adolescents universe, from a regional point of view which is characterized by a mix of socially represented cultures. In order to understand the topics related to adolescents culture, school and drama aspects, it was employed a theoretical support that defines important terminology to the comprehension of such cultural expression represented by literary relations associated to drama, namely culture, identity, imaginary, adolescence and school drama. The theoretical support employed also allowed the understanding of the culture and how values are shown and are articulated within the group, transcribed through the drama scripts. As a result, this study intends to contribute to the understanding of adolescents cultural identity as well as to further studies that involve the investigation of culture and literature in regional and school contexts.
O espaço escolar é um dos lugares onde a cultura é manifestada, integrando diferentes valores. Por isso, este estudo tem como objetivo analisar os valores culturais presentes nas produções escritas por adolescentes para a dramatização em período escolar. O estudo foi realizado por meio da análise de textos dramáticos produzidos por alunos de uma escola da rede particular de ensino da cidade de Caxias do Sul. A pesquisa utiliza o método da análise de conteúdo, tendo como corpus textos teatrais produzidos no período dos onze anos de existência da escola selecionada, os quais sinalizam alguns dos aspectos culturais valorizados no período da adolescência. Do estudo dos textos emergiram categorias culturais temáticas que se referem a: relações sociais: família e amizades; cultura regional: traços da cultura italiana e gauchesca; literatura e cinema e passado, futuro e meio ambiente; mídia e tecnologia. A abordagem desses assuntos define aspectos do universo da adolescência, considerado do ponto de vista regional e caracterizado pela mistura de culturas representadas socialmente. Na compreensão das questões culturais, escolares e teatrais, utilizou-se um aporte teórico que definiu alguns termos importantes para a compreensão das manifestações culturais por meio das representações literárias associadas ao teatro, tais como: cultura, identidade, imaginário, adolescência e teatro escolar. O referencial teórico utilizado permitiu o entendimento da cultura e de como os valores aparecem e são articulados nesse grupo, representados pelo texto teatral. Desse modo, o estudo contribui para a compreensão da identidade cultural na adolescência e para os estudos que envolvem a investigação da cultura e da literatura em contexto escolar e regional.
Keywords: Lingüística, Letras e Artes; Cultura; Adolescência; Identidade; Teatro escolar; Literatura; Identidade cultural; Sociologia cultural; Culture; Adolescence; Identity; School drama; Literature; Cultural identity; Cultural sociology